2020
DOI: 10.3390/foods9070947
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Probiotics: Functional Fruit Beverages and Nutraceuticals

Abstract: Over the last decade, fruit juice consumption has increased. Their rise in popularity can be attributed to the belief that they are a quick way to consuming a dietary portion of fruit. Probiotics added to fruit juices produce various bioactive compounds, thus probiotic fruit juices can be considered as a new type of functional foods. Such combinations could improve nutritional properties and provide health benefits of fruit juices, due to delivering positive health attributes from both sources (fruit juices an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 134 publications
(270 reference statements)
0
53
0
Order By: Relevance
“…The prevalence of DN in now growing worldwide and the treatments are very limited, therefore the reported effects of probiotics can allow clinicians to use these compounds as adjunct therapy. Probiotics are considered as safe (GRAS status: generally recognized as safe) [ 49 ]. Moreover, it was found that the use of probiotic did not have any negative effect on the renal functions [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of DN in now growing worldwide and the treatments are very limited, therefore the reported effects of probiotics can allow clinicians to use these compounds as adjunct therapy. Probiotics are considered as safe (GRAS status: generally recognized as safe) [ 49 ]. Moreover, it was found that the use of probiotic did not have any negative effect on the renal functions [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fruit juices have gained more attention in recent years as vehicles for probiotic delivery versus dairy products because there are more and more consumers who have shifted their interest to plant products, particularly vegetarians [ 13 , 17 , 18 ]. The main reasons for this turn are lactose intolerance, high cholesterol content of meat and dairy products, and allergic effects of milk proteins, which are limiting factors in the growth of dairy- or even meat-based probiotics [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main reasons for this turn are lactose intolerance, high cholesterol content of meat and dairy products, and allergic effects of milk proteins, which are limiting factors in the growth of dairy- or even meat-based probiotics [ 19 , 20 , 21 ]. In the past few years fruit juices have become very popular for probiotic delivery through lactic acid fermentation, as proposed by many researchers [ 18 , 22 , 23 ]. Regarding lactic acid fermentation of chokeberry juice, few research attempts have been recorded in the literature till now.…”
Section: Introductionmentioning
confidence: 99%
“…HVED (cold plasma) has been recently researched for enhancing extractions of various compounds from different raw materials. 98 In this technology, energy is presented directly in a liquid throughout a plasma channel formed by applying a current of high-voltage electrical discharge between two electrodes. Compared to PEF, HVED causes more damage to the product, influencing both the cell wall and membrane.…”
Section: Process and Proceduresmentioning
confidence: 99%
“…formation of free radicals), which consequently promotes cell structure damage and the creation of membrane pores. [94][95][96][97][98][99] The HVED extraction system is usually classified in three categories: batch, continuous and circulating extraction systems. The process mechanism is the same for all three categories, but the difference is between the device structures, which mostly refers to electrodes.…”
Section: Process and Proceduresmentioning
confidence: 99%